PENINGKATAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI KEGIATAN MERONCE PADA KELOMPOK B TAMAN KANAK-KANAK PKK TO’LEMO KABUPATEN LUWU - Yuliana S P; Syamsul Alam Ramli; Hajeni Hajeni (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2020)
This study aims to improve children's fine motor skills through group B Meronce activities at TK PKK To'lemo, Lamasi Timur District, Luwu Regency. The design of this research refers to Classroom Action Research, namely Planning, Implementation, Observation, and Reflection. This research will be conducted at TK PKK To Lemo Cokroaminoto which is located in Lemo Village, Lamasi Timur District, Luwu Regency. The data source of this research was the students of group B which consisted of 13 boys and 7 girls with a total of 20 children. Data collection techniques in this study were carried out by a) Observation, namely checklists, anecdotal notes, and works; b) Documentation. The data analysis technique was carried out by means of descriptive qualitative. The results of this study indicate that the activities carried out through meronce showed an increase from cycle 1 to cycle 2, the average of children's fine motor skills was 7.15 with a percentage of 35.75%. Based on this, through meronce activities for group B children at TK PKK To'lemo, Lamasi Timur District, Luwu Regency, it can improve children's fine motor skills. Based on this, this research is declared complete.